Perancangan Aplikasi Pembelajaran Bahasa Jawa Berbasis Android - Ayu Ernawati; Aries Saifudin (Teknik Informatika Universitas Pamulang, 2018)
The number of Javanese speakers is decreasing because many young people are not regularly using Javanese but rather use Indonesian, foreign languages, and slang languages. The structure of the Javanese and Indonesian is relatively similar. The Javanese language has a multilevel vocabulary so that it becomes a lot. Many and rarely used vocabularies make it easy to forget. Nowadays there are many people who use Android-based mobile devices. In this study proposed to make a Java language learning application based on Android to facilitate learning the Javanese language. The Java language learning application can be used by users to learn the Java language easily because it can use anytime and anywhere.